Bending DNA can repress a eukaryotic basal promoter and inhibit TFIID binding. - TenHarmsel, A (1995)
Previous studies indicated that repression by eve involves cooperative DNA binding and leads to the formation of a DNA loop which encompasses the DNA sequences normally bound by the RNA polymerase II general transcription factors. To test the general principle of whether bending of a basal promoter sequence can contribute directly to repression of transcription, a minicircle template of 245 bp was used. In a purified transcription system, transcription from the minicircular DNA is greatly reduced compared with that from the identical DNA fragment in linear form. Transcription is also reduced when the minicircle contains a single-stranded nick, indicating that transcription is reduced because of DNA bending, rather than any constraint on supercoiling. We show that the reduced transcription from the minicircle in these experiments is not due to a reduced rate of elongation by RNA polymerase II. Rather, repression occurs, at least in part, because binding of the general transcription factor TFIID to the minicircle is strongly inhibited compared with binding to the linear DNA. We suggest that bending DNA may be a mechanism by which eukaryotic transcription may be regulated, by modulating the activity of the general transcription factors.